2014
DOI: 10.1111/icad.12072
|View full text |Cite
|
Sign up to set email alerts
|

Species richness of associates of ants in the nests of red wood ant Formica polyctena (Hymenoptera, Formicidae)

Abstract: Ant nests are rich with various other fauna, and they may be seen as resources for these guest species. We studied the species richness and abundance of ant guests in the nests of Formica polyctena by addressing the resource concentration hypothesis, which predicts that nests in high densities would support higher species richness and abundance of specialised guests. In 12 nests we found 1562 individuals belonging to 70 taxa, of which beetles were the most species rich group. The resource concentration hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 23 publications
3
25
1
Order By: Relevance
“…We believe that as common soil animals within forest the oribatids may be able to choose their habitat spatially in relation to the condition most suitable for each species and therefore enter also to ant nest mounds to exploit the rich resources that those offer. In turn, it has been shown that for nest inhabiting beetles the existence of closely located and well connected nest mounds are essential (Härkönen & Sorvari, ) and the number of myrmecophilic species decreases with increasing mound isolation (Parmentier et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We believe that as common soil animals within forest the oribatids may be able to choose their habitat spatially in relation to the condition most suitable for each species and therefore enter also to ant nest mounds to exploit the rich resources that those offer. In turn, it has been shown that for nest inhabiting beetles the existence of closely located and well connected nest mounds are essential (Härkönen & Sorvari, ) and the number of myrmecophilic species decreases with increasing mound isolation (Parmentier et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Polygynous (several queens in one nest) and polydomous (form large colonies with a network of several nests) red wood ant F. polyctena was selected as the host ant species, since it is the dominant ant species in southern Finland (Collingwood, ; Seifert, ), and its nest mounds were the most common in the study area. Although F. polyctena shows a preference for coniferous forest, it maintains populations in various habitats including the studied oak forest (Seifert, ; Härkönen & Sorvari, ). Apart from F. polyctena several other mound‐building red wood ants of the F. rufa group occur on Ruissalo: F. lugubris , F. pratensis and F. rufa (J. Sorvari unpubl.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study several aspects of the colour patterns were considered, as both the shapes of melaninbased colour morphs, the percentage of melanized area and the Frouz et al, 2016), improve soil properties (Frouz & Jílková, 2008) and affect concentrations of macroelements in tree roots and thus regulate their growth (Ohashi et al, 2007). These insects regulate structure and biodiversity of forest plants and animal communities, contributing to seed dispersal (Gorb et al, 2000) and provide suitable habitats for numerous other invertebrates (Härkönen & Sorvari, 2014;Parmentier et al, 2014;Elo et al, 2016). Red wood ants, like other ants, provide various ecosystem services (Del Toro et al, 2012).…”
Section: Colour Pattern and Analysis Of Melanizationmentioning
confidence: 99%
“…We selected six beetle species belonging to five different families: Thiasophila angulata (Erichson, 1837), Leptacinus formicetorum (Märkel, 1841) (Staphylinidae), Dendrophilus pygmaeus (Linnaeus, 1758) (Histeridae), Monotoma angusticollis (Gyllenhal, 1877) (Monotomidae), Ptenidium formicetorum (Kraatz, 1851) (Ptiliidae) and Myrmechixenus subterraneus (Chevrolat, 1835) (Tenebrionidae). All selected species are commonly found inside F. polyctena nests, but they are rather unspecialized in the level of integration into colony [19,20]. Two representatives of Staphylinidae: Thiasophila angulata and Leptacinus formicetorum are predators, actively seeking out early developmental stages of ants (eggs and larvae) and other invertebrates inhabiting nests of red wood ants.…”
Section: Introductionmentioning
confidence: 99%